2008
DOI: 10.1186/1471-2164-9-327
|View full text |Cite
|
Sign up to set email alerts
|

The Hypocrea jecorina (Trichoderma reesei) hypercellulolytic mutant RUT C30 lacks a 85 kb (29 gene-encoding) region of the wild-type genome

Abstract: Background: The hypercellulolytic mutant Hypocrea jecorina (anamorph Trichoderma reesei) RUT C30 is the H. jecorina strain most frequently used for cellulase fermentations and has also often been employed for basic research on cellulase regulation. This strain has been reported to contain a truncated carbon catabolite repressor gene cre1 and is consequently carbon catabolite derepressed. To date this and an additional frame-shift mutation in the glycoprotein-processingglucosidase II encoding gene are the only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
105
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(116 citation statements)
references
References 43 publications
7
105
1
3
Order By: Relevance
“…One approach to depolymerization of plant cell wall polysaccharides involves using hydrolytic enzymes produced by bacteria and fungi (3). Toward achieving this goal, the filamentous fungus, Hypocrea jecorina (Trichoderma reesei) has been engineered, largely through random mutagenesis and screening, to produce elevated amounts of cellulases (4).…”
mentioning
confidence: 99%
“…One approach to depolymerization of plant cell wall polysaccharides involves using hydrolytic enzymes produced by bacteria and fungi (3). Toward achieving this goal, the filamentous fungus, Hypocrea jecorina (Trichoderma reesei) has been engineered, largely through random mutagenesis and screening, to produce elevated amounts of cellulases (4).…”
mentioning
confidence: 99%
“…The biochemical nature of these observations is unclear, but indicates a dependence of carbon catabolite repression on assimilation of these carbon sources. Seidl et al (2008) also showed that the H. jecorina RUT C30 and its ancestor NG 14 lack an 85-kb genomic fragment, missing additional 29 genes comprising transcription factors, enzymes of the primary metabolism and transport proteins. They reported that these mutations are not linked to the cre1 locus.…”
Section: Carbon Catabolite Repressionmentioning
confidence: 99%
“…The latter two carbon sources might reflect enhanced β-glucosidase activity, yet the rest of utilized carbon sources are catabolite repressing compounds and at this point, le Crom et al (2009) stressed that it is not clear whether this is a consequence of the cre1 mutation or it is due to the effect of other affected genes. Previously reported inverse carbon source utilization in correlation with enhanced cellulase production was detected by utilization of α-linked oligosaccharides and glycans (Seidl et al, 2008), and was complemented by the correlation between cellulase production and reduced growth on amino acids. le Crom et al (2009) discussed this phenotype to be related to an ability of the superior cellulase production strains to use a higher portion of their amino acid pool for synthesis of secreted proteins versus growth.…”
Section: Testing Gene Knockouts With Expected Phenotypesmentioning
confidence: 99%
See 2 more Smart Citations